Lentiviral haemopoietic stem-cell gene therapy in early-onset metachromatic leukodystrophy: an ad-hoc analysis of a non-randomised, open-label, phase 1/2 trial. Issue 10043 (30th July 2016) - Sessa, Maria; Lorioli, Laura; Fumagalli, Francesca; Acquati, Serena; Redaelli, Daniela; Baldoli, Cristina; Canale, Sabrina; Lopez, Ignazio D; Morena, Francesco; Calabria, Andrea; Fiori, Rossana; Silvani, Paolo; et al.
Summary: Background: Metachromatic leukodystrophy (a deficiency of arylsulfatase A [ARSA]) is a fatal demyelinating lysosomal disease with no approved treatment. We aimed to assess the long-term outcomes in a cohort of patients with early-onset metachromatic leukodystrophy who underwent haemopoietic stem-cell gene therapy (HSC-GT). Methods: This is an ad-hoc analysis of data from an ongoing, non-randomised, open-label, single-arm phase 1/2 trial, in which we enrolled patients with a molecular and biochemical diagnosis of metachromatic leukodystrophy (presymptomatic late-infantile or early-juvenile disease or early-symptomatic early-juvenile disease) at the Paediatric Clinical Research Unit, Ospedale San Raffaele, in Milan. Trial participants received HSC-GT, which consisted of the infusion of autologous HSCs transduced with a lentiviral vector encoding ARSA cDNA, after exposure-targeted busulfan conditioning. The primary endpoints of the trial are safety (toxicity, absence of engraftment failure or delayed haematological reconstitution, and safety of lentiviral vector-tranduced cell infusion) and efficacy (improvement in Gross Motor Function Measure [GMFM] score relative to untreated historical controls, and ARSA activity, 24 months post-treatment) of HSC-GT. For this ad-hoc analysis, we assessed safety and efficacy outcomes in all patients who had received treatment and been followed up for at least 18 months post-treatment on June 1, 2015. This trial is registered with ClinicalTrials.gov, number NCT01560182 . Findings: Between April, 2010, and February, 2013, we had enrolled nine children with a diagnosis of early-onset disease (six had late-infantile disease, two had early-juvenile disease, and one had early-onset disease that could not be definitively classified). At the time of analysis all children had survived, with a median follow-up of 36 months (range 18–54). The most commonly reported adverse events were cytopenia (reported in all patients) and mucositis of different grades of severity (in five of nine patients [grade 3 in four of five patients]). No serious adverse events related to the medicinal product were reported. Stable, sustained engraftment of gene-corrected HSCs was observed (a median of 60·4% [range 14·0–95·6] lentiviral vector-positive colony-forming cells across follow-up) and the engraftment level was stable during follow-up; engraftment determinants included the duration of absolute neutropenia and the vector copy number of the medicinal product. A progressive reconstitution of ARSA activity in circulating haemopoietic cells and in the cerebrospinal fluid was documented in all patients in association with a reduction of the storage material in peripheral nerve samples in six of seven patients. Eight patients, seven of whom received treatment when presymptomatic, had prevention of disease onset or halted disease progression as per clinical and instrumental assessment, compared with historical untreated control patients with early-onset disease. GMFM scores for six patients up to the last follow-up showed that gross motor performance was similar to that of normally developing children. The extent of benefit appeared to be influenced by the interval between HSC-GT and the expected time of disease onset. Treatment resulted in protection from CNS demyelination in eight patients and, in at least three patients, amelioration of peripheral nervous system abnormalities, with signs of remyelination at both sites. Interpretation: Our ad-hoc findings provide preliminary evidence of safety and therapeutic benefit of HSC-GT in patients with early-onset metachromatic leukodystrophy who received treatment in the presymptomatic or very early-symptomatic stage. The results of this trial will be reported when all 20 patients have achieved 3 years of follow-up. Funding: Italian Telethon Foundation and GlaxoSmithKline.